Kelarutan CdS dan CuS dalam Gelasi Mikroemulsi Water In Oil Sistem Air, Surfaktan SDBS dan Pentanol - Rahmi Fauziah; Minda Azhar; Hary Sanjaya; Ali Amran (Jurnal Periodic Jurusan Kimia UNP, 2020)
Surfactants are active compounds that act on the surface of a liquid, which can reduce the surface tension between oil and water. The purpose of this study was to determine the solubility of yellow and black inorganic pigments in water in oil microemulsion gelation, which was applied to ballpoint ink. The method used for sol preparation is the gelation method (sol-gel process). The sol gel process is the process of forming inorganic compounds through chemical reactions in solution, and occurs at a temperature of 65oC. The sol gel process undergoes a phase change from the colloid suspension (sol) and finally forms a network called a gel. Dye solubility was observed by the amount of yellow and black inorganic pigment solutes in water in oil microemulsion. The solubility of the yellow pigment is 0.096 grams, while the black pigment is 0.088 grams. To see the density of the pigment, a density test was carried out. The total density produced in yellow inorganic pigment is 0.933 gram / cm3 and black inorganic pigment is 0.914 gram / cm3. Measurement of the refractive index and turbidity (turbidity) to determine the homogeneity of the yellow and black pigments was carried out using an ABBE refractometer and a turbidimeter. The results of the refractive index measurement are associated with pigment solubility, the greater the pigment solubility, the higher the refractive index and turbidity values.